Short-Term Silymarin Supplementation After Kidney Transplantation Is Associated with Reduced Early Albuminuria: A Prospective Cohort Study - Matej Vnučák; Karol Graňák; Patrícia Kleinová; Tímea Jusková; Andrej Kollár; Katarína Ševčíková; Ivana Dedinská (Journal of Clinical Medicine, 2026)
Background: Early post-transplant albuminuria is associated with adverse graft and cardiovascular outcomes and may reflect ischemia–reperfusion injury-induced damage to the glomerular filtration barrier. However, evidence for safe adjunctive interventions targeting these early pathophysiological processes remains limited. Methods: In this single-center prospective cohort study with historical controls, adult kidney transplant recipients transplanted between January 2020 and September 2022 served as controls, while consecutive recipients transplanted from October 2022 onward received adjunctive silymarin (900 mg/day for 30 days) in addition to standard immunosuppression. The principal renal outcome was UACR assessed during the first 3 months post-transplant. A ≥25% reduction in UACR between Months 1 and 3 was additionally evaluated as an exploratory responder outcome. Secondary outcomes included estimated glomerular filtration rate (eGFR), lipid profile parameters, tacrolimus exposure, and safety. Results: A total of 136 patients (78 silymarin-treated and 58 controls) were included. UACR was consistently lower in the silymarin group at months 1–3. In multivariable analysis, silymarin treatment was independently associated with lower UACR at month 3. In an exploratory responder analysis, a ≥25% reduction in UACR between Months 1 and 3 occurred more frequently in silymarin-treated patients (OR 3.28, 95% CI 1.38–7.79; p = 0.007). eGFR trajectories were similar between groups. No consistent independent effects on lipid parameters were observed after adjustment. Tacrolimus exposure and adverse event rates were comparable between groups. Conclusions: Short-term silymarin exposure initiated early after kidney transplantation was associated with lower UACR during the first three post-transplant months. These findings support a potential targeted effect on early glomerular injury and suggest that silymarin may represent a safe adjunctive strategy to modulate early post-transplant risk.